Ergenlerin benlik algıları ile iyi oluş halleri arasındaki ilişkinin incelenmesi: Diyarbakır Şehitlik semti örneği - Kaya, İbrahim (İstanbul Sabahattin Zaim Üniversitesi, 2022)
Ergenlik dönemi, bireyler için çocukluktan yetişkinliğe giden yolda bir geçittir. Bu dönemde ergenlerin karşılaştıkları durumlara karşı benlik algıları verdikleri tepkileri, psiko-sosyal gelişimlerini ve sağlıklarını etkileyebilemektedir. Bu araştırmanın amacı, Diyarbakır ilinin dezavantajlı ve sosyal hizmete ihtiyaç duyan bireylerin fazlaca yaşadığı Şehitlik Semti'nde yaşayan ergenlerin benlik algıları ile iyi oluşları arasındaki incelemektir. Bu araştırmada nicel araştırma yöntemlerinden ilişkisel tarama modeli kullanılmıştır. Çalışmada kolayda örnekleme yöntemi belirlenen Diyarbakır Şehitlik Semtinde yaşayan 13-18 yaş aralığındaki 357 dezavantajlı ergene ulaşılmıştır. Araştırmada demografik bilgi formu, sosyal karşılaştırma ölçeği ile ergenler için beş boyutlu iyi oluş modeli (epoch) ölçeği kullanılmıştır. Yapılan istatistiksel analiz sonucunda verilerin normal dağıldığı görüldüğü için araştırmada frekans, t testi ve one way ANOVA olmak üzere parametrik testler uygulanmıştır. Araştırma sonuçlarına bakıldığında Diyarbakır şehitlik semtinde yaşayan ergenlerin demografik özellikleri ile benlik algıları ve iyi oluş halleri arasında anlamlı bir farklılaşma bulunmaktadır. Ergenlerin benlik algıları ile iyi oluş halleri arasında pozitif yönde anlamlı bir ilişki vardır. Ergenlerin benlik algıları arttıkça iyi oluş halleri de olumlu yönde artış göstermektedir. Ergenlerin benlik algılarının iyi oluş halleri için belirleyici bir faktör olduğu anlaşılmıştır.

Adolescence is a gateway on the path from childhood to adulthood for individuals. The reactions of adolescents to the situations they face during this period in terms of their self-perception, it can affect their psycho-social development and health. The aim of this study is to examine the relationship between self-perception and well-being of adolescents living in the Martyrdom District, where disadvantaged and needy individuals of Diyarbakir province live a lot, and the decency of the individuals who need social services. In this study, a relational screening model was used as one of the quantitative research methods. In the study, 357 disadvantaged adolescents aged 13-18 years living in the Martyrdom District of Diyarbakir, whose sampling method was determined in the study, were reached. In the research, demographic information form, social comparison scale and five-dimensional well-being model (epoch) scale for adolescents were used. As a result of the statistical analysis, it was seen that the data were distributed normally, parametric tests such as frequency, t test and one way ANOVA were applied in the study. The results of the research, considering the sociodemographic characteristics of adolescents who live in the neighbourhood of the martyrdom of Diyarbakir and the perceptions of self and well-being, there is a significant differentiation between a state of. There is a positive significant relationship between adolescents' self-perceptions and their well-being. Decency is a positive relationship between self-perceptions and well-being. As the self-perception of adolescents increases, their well-being also increases positively. It has been understood that adolescents' self-perceptions are a determining factor for their well-being.
Investigation of the relationship between adolescents' self-perception and well-being: An example of the Şehitlik district of Diyarbakır
Keywords: Ergenlik; Benlik algısı; İyi oluş; Güçlendirme yaklaşımı; Şehitlik semti; Adolescence; Self-perception; Well-being; Empowerment approach; Şehitlik district